EFISIENSI SALURAN PEMASARAN KOMODITAS BAYAM DI KELURAHAN SIANTAN HILIR KECAMATAN PONTIANAK UTARA KOTA PONTIANAK - Raja Nammy Petrus Purba; Dewi Kurniati; Anita Suharyani (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2022)
Spinach is one of the agricultural commodities that is widely cultivated in Pontianak City. North Pontianak District is a center for growing spinach in Pontianak City with a planted area of 216 (ha) and production of 8,006 (ku) or around 76% of the total spinach production in the Pontianak City. There are two types of spinach that are most commonly cultivated in Siantan Hilir Village, North Pontianak District, namely spinach (Amaranthus tricolor). The purpose of this study was to analyze the pattern of marketing channels, marketing margins, farmer's share and efficiency of spinach marketing channels in Siantan Hilir Village, North Pontianak District, Pontianak City. The results indicate that there are 4 marketing channels of spinach. The lowest marketing margin value of spinach and the highest farmer's share is in channel 1, while the lowest margin and farmer's share are also found in channel 1. The most efficient marketing efficiency value of spinach is found in channel 3 which is 2.70 %, meanwhile, the most efficient marketing channel is in channel 2 with an efficiency value of 2.58%.